Development of Skin Care Routine Support System - Noorhuzaimi, Mohd Noor; Nur Jannah, Muhamad; Noor Azida, Sahabudin; Zuriani, Mustaffa (American Scientific Publisher, 2018)
Skin Care Routine Support System is a system to help people how to take care their facial skin. There are differences routine that needs to use based on different skin types. In order to determine the skin type, the people need to have knowledge about the combination of skin condition. This can cause difficulty for the people to analyse their skin type if they cannot able to determine their combination skin condition and do not have deep knowledge about skin symptom. As for a solution, we have proposed a skin care routine decision support system using the knowledge-base. The system able to predict the user skin type based on environment, age, gender, sleeping hour and skin conditions that will be input by the user. The user input then will be processed by using a set of score rules to determine the type of skin based on maximum rate. The rules are developed based on general observation from the web, journal paper, and books. After the skin type determination process finished, the system provides tips and knowledge of common chemical ingredient that needs to be avoided by the user. The testing process will be conducted for two types of correspondence which are public user and expert. The system functionality and system knowledge testing will be got from the public user, while the content, rules, and output will be got from the expert. Expected results for the feedback are the system able to support the user to determine their skin type and give knowledge to the user in order to select correct routine and suitable product.